Arteriovenous Fistula Failure due to Two Straight Shunts Formation at Draining Vein - Tong, Yan Qing (African Networks on Ethnomedicines, 2013)
A 48-year-old asian man was admitted to hospital for the consideration of hemodialysis (HD). An adequate site was decided on for the AVF after Doppler ultrasonography examination of radial artery and cephalic vein. The AVF was formed under local anaesthetic at his right wrist. When seen at the clinic appointment one month later, the AVF was not working. The subsequent Doppler ultrasonography examination revealed two straight shunts at draining vein. The failure of AVF is due to impaired outflow following reduction of the resistance between draining vein and peripheral venous system.